2016
DOI: 10.3233/mnm-160056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artocarpus altilis fruit based-diet on liver and kidney function indices on alloxan-induced diabetic rats

Abstract: BACKGROUND:The prevalence of diabetes mellitus continues to increase alarmingly in spite of years of intensive research. The need to explore alternative therapy such dietary and phytotherapy has been gaining attention in the management/treatment of diabetes mellitus. OBJECTIVE: The present research work was carried out to investigate the biochemical indices in the liver and kidney of alloxan-induced diabetic rats fed with Artocarpus altilis fruit based-diet. METHODS: Diabetes was induced by a single intraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…Few studies have been published on the effects of extracts or essential oils from P. aduncum , M. citrifolia , and A. altilis on the hematological profiles of birds. The results obtained in the present study were like those reported in previous studies on birds ( 49 ), rats, and mice (Schuktz et al, 2017); ( 50–53 ), where similar hematological profiles were obtained on increase in the levels of P. glabratum , P. aduncum , M. citrifolia , and A. altilis extracts. However, few previous studies evaluating leaf powders of plants, such as Moringa oleifera and Azadirachta indica , demonstrated an increase in the hematological profiles of the broiler chickens ( 46 , 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have been published on the effects of extracts or essential oils from P. aduncum , M. citrifolia , and A. altilis on the hematological profiles of birds. The results obtained in the present study were like those reported in previous studies on birds ( 49 ), rats, and mice (Schuktz et al, 2017); ( 50–53 ), where similar hematological profiles were obtained on increase in the levels of P. glabratum , P. aduncum , M. citrifolia , and A. altilis extracts. However, few previous studies evaluating leaf powders of plants, such as Moringa oleifera and Azadirachta indica , demonstrated an increase in the hematological profiles of the broiler chickens ( 46 , 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although the study by Ajiboye et al (2016) on T. africana fruit/ seed suggested its beneficial use in the management of diabetes mellitus, our study on processed T. africana seed gave contrary results, although the duration of our study was short. Furthermore, information on the effect of consumption of processed T. africana seed on the lipid profile of humans or animals is missing in literature.…”
Section: Introductioncontrasting
confidence: 66%
“…Oboh et al (2015) reported the glycemic index (GI) of breadfruit seed to be about 64.5, which places it as an intermediate GI crop based on the classification of GI by Brand-Miller et al (2003). On the other hand, Ajiboye et al (2016) reported the hypoglycemic action of this plant in experimentally induced diabetic rats, and the findings of this study suggest that the processing of this plant by boiling (which is the form in which it is eaten in typical diets) affects its reported hypoglycemic action. This variation between our results and those of Ajiboye and colleagues could be attributed to the fact that, while Ajiboye and colleagues worked on raw seeds, we worked on cooked seeds, and cooking has been reported to affect the nutrient constituents and the digestibility of starches in foods, which could also affect their glycemic indices (Capriles et al, 2008;Eleazu et al, 2016;Eleazu et al, 2017).…”
Section: Discussionmentioning
confidence: 57%
“…Although the hypoglycemic actions of the roots and seeds of this plant have been reported (Ajiboye et al, 2016;Olatunji et al, 2014;Oyelola et al, 2007), the effect of processing the seed (the edible part) on its hypoglycemic action has not been reported. This is especially important as the seed is eaten after being processed, and different food processing techniques could affect the starch digestibility of foods, which in essence will affect the glycemic indices of these foods.…”
Section: Introductionmentioning
confidence: 99%